Challenges And Opportunities In Achieving Defense Industry Independence: An In-Depth Analysis Of Policy Implementation At PT Pindad (International Journal of Environmental Sciences, 2025)
This study examines the challenges and opportunities in achieving defense industry independence at PT Pindad, a key state-owned enterprise in Indonesia. Despite policies like Law Number 16 of 2012 and the Minimum Essential Force (MEF) program aimed at reducing reliance on imports and enhancing self-sufficiency, PT Pindad faces significant hurdles, including dependency on foreign raw materials, limited technology transfer, and regulatory inefficiencies. The study suggests that strategic measures, such as increased investment in R&D, effective technology transfer, and stronger collaboration between government, private sectors, and academia, are essential for overcoming these challenges and strengthening Indonesia's defense industry. By analyzing successful examples from countries like China and Turkey, the study emphasizes the importance of integrated and adaptive policies to foster technological innovation, enhance local supply chains, and improve competitiveness. Adopting a collaborative approach under the Penta-Helix model, which brings together government, businesses, academia, communities, and media, is recommended to accelerate the development of a self-sufficient and resilient defense sector in Indonesia.